Neurodiversity in Human Resource Management: A Bibliometric Analysis and Research Agenda for Indonesia - Andi Rahmawati (Economics and Business Journal (ECBIS), 2026)
Neurodiversity conceptualizes autism, attention-deficit/hyperactivity disorder (ADHD), dyslexia, and related cognitive differences as natural variations in human cognition rather than individual deficits. Although this perspective has gained increasing attention in human resource management (HRM), the intellectual structure and relevance of the existing literature to the Indonesian context remain insufficiently understood. This study maps the development of global research on neurodiversity and HRM and identifies research priorities for Indonesia. A bibliometric analysis was conducted using 993 records retrieved through a Boolean search combining neurodiversity- and HRM-related terms. Following a PRISMA-guided screening process, keyword co-occurrence, density, overlay, and total link-strength analyses were performed using VOSviewer. The analysis identified 43 dominant terms grouped into four thematic clusters: (1) inclusive HRM and diversity management, (2) workplace accommodation and disclosure, (3) intervention and school-to-work transition, and (4) ADHD and occupational mental health. The findings indicate that autism spectrum disorder and ADHD remain the most prominent topics in the literature. The field has gradually shifted from predominantly clinical and educational perspectives in 2020–2021 toward workplace accommodation in 2022 and more strategic HRM-oriented discussions during 2023–2024. However, link-strength analysis reveals that relationships between core HRM concepts and issues of accommodation, disclosure, and occupational mental health remain relatively fragmented. Moreover, Indonesia-specific and developing-country perspectives are absent from the dominant keyword structure. These findings demonstrate a substantial geographical and conceptual research gap. Accordingly, the study proposes five priority research themes to advance neurodiversity-inclusive HRM in Indonesia and provides a foundation for future empirical, policy-oriented, and organizational research.